Histological characterization of HIFU lesions - Ian Rivens; Chaturika Jayadewa; Petros Mouratidis; Gail ter Haar (International Journal of Hyperthermia)
Background: High intensity focused ultrasound (HIFU) can destroy tissue by thermal ablation which may be accompanied by acoustic cavitation and/or tissue water boiling, but the biological and histological effects of these treatments have not been fully documented. Here, detailed histological analysis over time using well characterized HIFU exposures in in vivo rat livers is described.Methods: Exposures used invoked either (i) thermal, with acoustic cavitation and/or tissue water boiling or (ii) predominantly thermal damage. Cavitation activity was detected using both active and passive methods. Histological assessment involved hematoxylin and eosin (H&E), picrosirius red and immunohistochemical staining.Results: Distinct concentric damage regions were identified after HIFU exposures. The outermost ring showed a red H&E-stained rim that was characterized by hemorrhage. The adjacent inner band appeared white due to increased extracellular spaces. The morphology of the next zone depended on the exposure. Where there was no tissue acoustic cavitation/water boiling, this was the lesion center, in which heat-fixed cells were seen. Where acoustic cavitation/boiling occurred, a centermost zone with irregular holes up to several hundred microns across was seen. Cleaved caspase-3 and Hsp70 staining in the periphery of both types of HIFU exposures was seen within the outermost ring of hemorrhage, where an inflammatory response was also observed. By day 7, a distinct acellular region in the center of the HIFU lesions had been created.Conclusions: These results identify the morphological effects and elucidate the similarities and differences of HIFU-induced thermal lesions in the presence or absence of acoustic cavitation/tissue water boiling.